The International Atomic Energy Agency's Safeguards System - Andrés, Gabriel Eugenio (2008)
Entrusted with the responsibility of establishing and administering the international safeguards system with the purpose of ensuring that nuclear energy would not be used for furthering military purposes, the International Atomic Energy Agency (hereinafter IAEA or the Agency) is a key piece of the international system for the maintenance of world peace and security. Despite the initial enthusiasm surrounding the foundation of the IAEA in the 1950s, it required several years for the Agency's safeguards to be accepted and applied in a broad manner. Since the beginning the safeguards system evolved along the progress of nuclear technology and most importantly in light of the development of the geopolitical context and the commitment showed by the international community in critical circumstances. Hence, in the same manner the discovery of the Iraqi clandestine nuclear weapons programme after the 1990-1991 Gulf War posed a serious challenge to the safeguards system, the IAEA is currently dealing with two most serious international conflicts involving States arguably with nuclear ambitions, namely: the Democratic Peoples Republic of Korea (hereinafter North Korea or DPRK) and the Islamic Republic of Iran (hereinafter Iran). Besides, the events of 11 September 2001 changed the system of international relations radically and posed a serious challenge to the same foundations of the world legal order in which the IAEA is a significant actor. The present article aims to provide the reader with a clear idea of the role and work of the IAEA and its safeguards system in the field of nuclear non-proliferation verification as well as the current challenges to the international safeguards regime. It is thus hoped that the concepts developed in this work may contribute to a better understanding and analysis of international conflicts involving present or potential nuclear proliferation threats.